Tissue Hypoperfusion, Hypercoagulopathy, and Kidney and Liver Dysfunction after Ingestion of a Naphazoline-Containing Antiseptic. (7th May 2017) - Ono, Yuko; Ono, Nozomi; Shinohara, Kazuaki
Abstract : Naphazoline is a peripheral α 2 -adrenergic receptor agonist commonly used as a topical decongestant. In Japan, over-the-counter antiseptics often contain naphazoline to effect local hemostasis. We present the first case involving the development of hypercoagulopathy, with kidney and liver dysfunction, following a naphazoline overdose. A 22-year-old Japanese woman with a history of depression ingested 160 mL of a commercially available antiseptic containing 0.1% naphazoline. Three days later, she was brought to the emergency department because of general fatigue, nausea, and vomiting. Physical examination revealed cool, pale extremities. Laboratory data showed evidence of severe kidney and liver dysfunction (creatinine, 9.2 mg/dL; alanine aminotransferase, 2948 IU/L), hypercoagulation (D-dimers, 58.3  μ g/mL), and thrombocytopenia (platelet count, 90, 000/ μ L). After infusion of normal saline, intravenous administration of alprostadil, and hemodiafiltration, her organ function completely recovered. Because both the kidney and liver express α 2 -adrenergic receptors, their failure was likely associated with naphazoline overdose-induced hypoperfusion. The most plausible causes of hypercoagulation are peripheral low perfusion and subsequent microthrombus formation. This case illustrates that severe organ dysfunction can occur following over-the-counter antiseptic ingestion and serves as a caution for both drug manufacturers and healthcare professionals.